PERENCANAAN SISTEM PEMBELAJARAN ADAPTIF DALAM MENGHADAPI TANTANGAN PENDIDIKAN MODERN - Siti Nurhopipah; Eneng Ulfatullailah; Ahmad Subagyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This paper aims to examine the planning of adaptive learning systems in facing the challenges of modern education. The planning of the learning system is compiled and designed so that learning can be effective and efficient according to the needs of diverse students, so that this adaptive learning can produce a learning experience based on the personality, interests, and performance of students to achieve goals such as improving student academics, student satisfaction, an effective learning process and so on. This research will discuss various aspects related to adaptive learning, ranging from basic concepts, implementation, to its impact on student learning outcomes. It is hoped that the results of this research can contribute to the development of more effective and efficient learning models, as well as inspire educators to utilize technology in improving the quality of education. The data collection in this writing uses literature review or literature review by taking sources from journals, books, and other scientific works. By designing this adaptive learning system, it will increase the effectiveness of students in the learning process.